2020
DOI: 10.1001/jamanetworkopen.2020.23262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Concordance Between Original Death Certifications and an Expert Panel Process in the Determination of Sudden Unexplained Death in Childhood

Abstract: Key Points Question Does the US death investigation system underestimate the frequency of sudden unexplained death in childhood (SUDC)? Findings In this case series of the SUDC Registry and Research Collaborative, 2 forensic pathologists from a pool of 13 independently reviewed 100 cases of SUDC. These reviewers were discordant with the original certifier’s cause of death opinion in 40% of cases, including 28 cases originally considered accidental or natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Sudden unexplained death in childhood (SUDC) is now a leading cause of death in toddlers (children 1–4 years of age). Although hundreds of SUDC cases are certified by medical examiners each year—392 cases were recorded by the CDC in 2018—in a recent study by Crandall et al [ 64 ], experts disagreed with the original certified cause-of-death in 40 % of cases, including many that were originally considered accidental or natural but adjudicated as "unexplained." There is a low rate of consistency and precision in death certification of SUDC, so true SUDC incidence is likely to be higher than official rates reported by the CDC.…”
Section: Discussionmentioning
confidence: 99%
“…Sudden unexplained death in childhood (SUDC) is now a leading cause of death in toddlers (children 1–4 years of age). Although hundreds of SUDC cases are certified by medical examiners each year—392 cases were recorded by the CDC in 2018—in a recent study by Crandall et al [ 64 ], experts disagreed with the original certified cause-of-death in 40 % of cases, including many that were originally considered accidental or natural but adjudicated as "unexplained." There is a low rate of consistency and precision in death certification of SUDC, so true SUDC incidence is likely to be higher than official rates reported by the CDC.…”
Section: Discussionmentioning
confidence: 99%
“…Cases are referred from multiple sites, including NYU, Columbia University, the Mayo Clinic (Minnesota), and over 30 clinical and forensic collaborators at medical examiner and coroner offices. Ancillary analyses done at autopsy [ 8 ] included microbiology, with various testing performed ( n = 17, all cases were not necessarily tested for all of the same viruses/bacteria). Of the cases with microbiology testing, 4/17 had positive post-mortem virology from respiratory and brain samples that were not considered as contributing to COD.…”
Section: Methodsmentioning
confidence: 99%
“…There have been few molecular studies in SUDC and several related studies in sudden unexpected infant death (SUID) cases (< 1 year of age). Genetic variants may influence SUDC risk, particularly neurological and/or cardiomyopathies [ 8 , 22 , 24 , 29 , 52 ]. De novo mutations that occur post-zygotically can result in somatic mosaicism and occur in SUDC and SUDEP cases, which can influence brain development in the form of abnormal neuronal migration, brain overgrowth disorders, as well as epileptic encephalopathies, intellectual disability, autism, and neuropsychiatric diseases [ 10 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children and young adults are less likely to suffer SCA compared to middle-aged and older persons 4, 5 . Autopsy results fail to reveal an explanation for SCA in approximately 40% of cases 6 and the attributed cause of death may be inaccurate 7 . Studies using genetic testing have revealed a significant portion (∼12-30%) of children/young adults with sudden cardiac death (SCD) that have pathogenic rare variants in genes associated with arrhythmic syndromes and cardiomyopathy 6, 8 .…”
Section: Introductionmentioning
confidence: 99%